Aggregate of metal oxyhydroxide and method for producing metal oxyhydroxide
By heating metal carbonate in high pressure and hydrogen peroxide steam atmosphere, metal oxygen hydroxide particles in the shape of needle-like are prepared and large-size polymers are formed, which solves the problem of easy destruction of existing manganese oxygen hydroxide particles and achieves wider application potential.
Patent Information
- Application Number
- JP2023166399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
The existing manganese oxygen oxyhydroxyoxide particles are easily destroyed under the action of external forces and cannot form effective polymers, which limits their use in applications such as filtration.
Needle-like-shaped metal oxygenhydroxide particles were prepared by heating the metal carbonate in a high pressure and hydrogen peroxide steam atmosphere, and polymerization was formed by polymerization with a maximum diameter of 1 mm or more.
The production of stable and polymerizable metal oxygenhydroxide polymers is achieved, enhancing its performance in filtration, sound-absorbing materials, adsorbents and other applications.
Smart Images

Figure 2025056887000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aggregate of a metal oxyhydroxide. The present invention also relates to a method for producing a metal oxyhydroxide. [Background technology]
[0002] Metal oxyhydroxides can be used for various purposes. For example, manganese oxyhydroxide can be used as a raw material for lithium manganese-based composite oxides, which can be used as a positive electrode material for lithium ion batteries. Various techniques have been proposed so far for metal oxyhydroxides and methods for producing them (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-105538 A Summary of the Invention [Problem to be solved by the invention]
[0004] The manganese oxyhydroxide disclosed in Patent Document 1 is characterized by being a particle that does not aggregate. On the other hand, the aggregates formed by the aggregation of particles also have their own applications. For example, since the aggregates are porous, they can be used as filters. However, even if an external force is applied to the particles disclosed in Patent Document 1 to form them into aggregates, the particles will be destroyed and it is thought that this will not be successful.
[0005] An object of one aspect of the present invention is to provide a novel method for producing a metal oxyhydroxide, which can produce an aggregate of metal oxyhydroxide particles. [Means for solving the problem]
[0006] The present invention includes the following aspects. <1> An aggregate of metal oxyhydroxide particles, The metal is a metal that can have an oxidation state +III. Aggregates. <2> The metal that can have an oxidation number of +III is at least one selected from the group consisting of manganese, cobalt, iron, aluminum, nickel, and vanadium. <1> The aggregate according to claim 1. <3> The metal oxyhydroxide particles are acicular particles. <1> or <2> The aggregate according to claim 1. <4> The aspect ratio (ratio of major axis to minor axis) of the acicular particles is 3 or more. <3> The aggregate according to claim 1. <5> The maximum diameter of the aggregate is 1 mm or more. <1> ~ <4> 2. The aggregate according to claim 1 . <6> 1. A method for producing a metal oxyhydroxide, comprising the step of heating a metal carbonate under pressure and in an atmosphere of hydrogen peroxide vapor, The metal carbonate is a carbonate of a metal that can have an oxidation number of +III. Manufacturing method. <7> The metal that can have an oxidation number of +III is at least one selected from the group consisting of manganese, cobalt, iron, aluminum, nickel, and vanadium. <6> The manufacturing method described in <8> The metal oxyhydroxide is in the form of particles or aggregates thereof. <6> or <7> The manufacturing method described in <9> The particles are acicular particles. <8> The manufacturing method described in <10> The aspect ratio (ratio of major axis to minor axis) of the acicular particles is 3 or more. <9> The manufacturing method described in <11> The maximum diameter of the aggregate is 1 mm or more. <8> The manufacturing method described in Effect of the Invention
[0007] According to one aspect of the present invention, there is provided a novel method for producing a metal oxyhydroxide, which is capable of producing an aggregate of metal oxyhydroxide particles. [Brief description of the drawings]
[0008] [Figure 1] 1 is a SEM image of an aggregate of manganese oxyhydroxide particles obtained in Example 1. [Diagram 2] The left panel is a graph showing the production rate of manganese oxyhydroxide in Example 1. The right panel is a graph showing the crystalline phase fraction in Example 1. [Diagram 3] 1 is a SEM image of an aggregate of manganese oxyhydroxide particles obtained in Example 2. [Figure 4] 1 is a SEM image of an aggregate of manganese oxyhydroxide particles obtained in Example 2. [Diagram 5] 1 is an XRD spectrum showing a crystalline phase in Example 2. [Figure 6] 1 is an XRD spectrum showing a crystalline phase in Example 2. [Figure 7] 1 is a graph showing the pore size distribution in Example 2. [Figure 8] Photographs showing the appearance of the manganese oxyhydroxide particle aggregates used as a filter in Example 3. Panel a shows the aggregates before use in filtration. Panel b shows the aggregates with Li2CO3 trapped therein after use in filtration. Panel c shows the aggregates with Li2CO3 trapped therein that were heated at 600°C for 2 hours. [Figure 9] 1 shows SEM images of an aggregate of manganese oxyhydroxide particles used as a filter in Example 3. Panel a shows a cross section through the thickness of the aggregate, and Panel b shows the surface of the aggregate after heating while trapping Li2CO3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An example of an embodiment of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and may be modified in various ways within the scope of the claims. An embodiment that combines technical means described in different embodiments is also included in the technical scope of the present invention.
[0010] Unless otherwise specified in this specification, "A to B" expressing a numerical range means "A or more, and B or less."
[0011] [1. Agglomerates of metal oxyhydroxide particles] One aspect of the present invention is an aggregate of metal oxyhydroxide particles. The aggregate of particles refers to an object in which a plurality of particles are aggregated to form an integrated mass. The particles contained in the aggregate may be integrated by partial fusion, may be integrated by intertwining particle shapes, or may be integrated due to forces acting between particles (such as electrostatic interactions). The number of particles contained in one aggregate may be, for example, 10 or more, 20 or more, or 30 or more.
[0012] The metal contained in the metal oxyhydroxide is a metal that can have an oxidation number of +III. Such a metal can be converted from a metal carbonate to a metal oxyhydroxide in the production method described below. Examples of metals that can have an oxidation number of +III include manganese, cobalt, iron, aluminum, nickel, and vanadium. In one embodiment, the metal is manganese.
[0013] The aggregate may contain a crystalline phase other than the metal oxyhydroxide. The crystalline phase fraction of the aggregate which is the metal oxyhydroxide may be 50% by weight or more, 70% by weight or more, 90% by weight or more, or 95% by weight or more, where the total weight of the crystalline phase is 100% by weight. The crystalline phase and its fraction are analyzed by powder X-ray diffraction (XRD).
[0014] In one embodiment, the metal oxyhydroxide particles forming the aggregates are acicular particles. The acicular particles refer to particles having a large aspect ratio (ratio of major axis / minor axis). The aspect ratio of the acicular particles can be, for example, 3 or more, 3.5 or more, 4 or more, 4.5 or more, or 5 or more. The major axis of the acicular particles can be, for example, 0.1 to 10 μm. The minor axis of the acicular particles can be, for example, 0.01 to 3 μm. The shape and aspect ratio of the particles are measured based on a scanning electron microscope image (SEM image).
[0015] Since the aggregate contains multiple particles, it may have a certain size. In one embodiment, the maximum diameter of the aggregate may be 1 mm or more, 3 mm or more, or 5 mm or more. The maximum diameter refers to the maximum distance that can be taken by two parallel planes when the aggregate is sandwiched between the two planes.
[0016] The manganese oxyhydroxide disclosed in Patent Document 1 is non-aggregated, and its size is on the order of micrometers. Therefore, the aggregate according to one embodiment of the present invention can be a much larger object than the manganese oxyhydroxide disclosed in Patent Document 1. Therefore, the aggregate opens up the possibility of various applications (filters, sound absorbing materials, adsorbents, catalysts, electrodes, etc.) that could not be realized if the particles were used as they are.
[0017] In one embodiment, the aggregate is porous. The porous aggregate can be suitably used as a filter, etc. The average pore size of the porous aggregate can be, for example, 0.1 to 1 μm. The average pore size is measured by mercury intrusion porosimetry.
[0018] The aggregates can be used as filters, etc. For example, if an aggregate of manganese oxyhydroxide particles is used as a filter to capture lithium in a solution, and then the filter is heated, lithium manganate can be produced. Since lithium manganate is used as a positive electrode material for lithium-ion batteries, the above-mentioned method can also be applied to the reuse of discarded secondary batteries.
[0019] 2. Method for Producing Metal Oxyhydroxide A method for producing a metal oxyhydroxide according to one embodiment of the present invention includes a step of heating a metal carbonate under pressure in an atmosphere of hydrogen peroxide vapor. The metal carbonate is a carbonate of a metal whose oxidation state can be +III. Although this is merely a speculative mechanism, it is believed that the oxidation state of the metal atom (M) increases from +II to +III as the reactions of the following formulas (1) to (3) proceed, and the reaction of formula (A) proceeds overall. 3MCO3+H2O2→M3O4+3CO2+H2O (1) M3O4+3 / 2H2O2→3MOOH+O 2- (2) O 2- +H2O→H2O2(3) 3MCO3+3 / 2H2O2→3MOOH+3CO2(A)
[0020] Examples of metals that can have the oxidation state +III are listed in Section [1].
[0021] The lower limit of the pressure during heating may be 0.1 MPa or more or 0.2 MPa or more. The upper limit of the pressure during heating may be 4.5 MPa or less, 3 MPa or less, 2.5 MPa or less, 2 MPa or less, or 1.5 MPa or less. The lower limit of the heating temperature may be 80°C or more or 100°C or more. The upper limit of the heating temperature may be 250°C or less or 200°C or less. The lower limit of the heating time may be 0.5 hours or more, 1 hour or more, or 2 hours or more. The upper limit of the heating time may be 48 hours or less, 36 hours or less, or 24 hours or less.
[0022] The hydrogen peroxide vapor is generated, for example, by heating an aqueous hydrogen peroxide solution. The lower limit of the concentration of the aqueous hydrogen peroxide solution at this time may be 1 vol% or more, 3 vol% or more, or 5 vol% or more. The upper limit of the concentration of the aqueous hydrogen peroxide solution may be 50 vol% or less, 40 vol% or less, or 30 vol% or less. When exposing the metal carbonate to hydrogen peroxide vapor, it is preferable to prevent the metal carbonate from coming into contact with the aqueous hydrogen peroxide solution in the liquid phase.
[0023] The above-mentioned production conditions are merely examples, and a person skilled in the art can produce a metal oxyhydroxide having desired physical properties (particle shape, pore size, etc.) within the scope of ordinary effort by appropriately changing various production conditions (in addition to those mentioned above, the volume of the container in which the metal carbonate is heated, etc.).
[0024] The shape of the metal oxyhydroxide obtained by this manufacturing method is not particularly limited. In one embodiment, the manufacturing method produces metal oxyhydroxide particles. In one embodiment, the manufacturing method produces aggregates of metal oxyhydroxide particles. The structural features of the metal oxyhydroxide particles and the aggregates are as described in Section [1].
[0025] In one embodiment, a preformed metal carbonate is used as a raw material and heated under pressure and in an atmosphere of hydrogen peroxide vapor. According to such a manufacturing method, an aggregate of formed metal oxyhydroxide particles is obtained. A molded body of metal carbonate is obtained, for example, by pressurizing metal carbonate particles filled in a container. The pressurization may be combined with heating or contact with pressurized water. The method for manufacturing a compressed body of manganese carbonate has been described in detail in a previous report by the present inventor (Takahiro Kozawa (2022) "Microstructural development of MnCO3 microsphere compacts through hydrothermal hot-pressing" Journal of the European Ceramic Society, vol.42, Issue 4, pp.1530-1536). EXAMPLES
[0026] Example 1 Using manganese carbonate particles as a raw material, an aggregate of manganese oxyhydroxide particles was produced by the following specific procedure. 1. 5 mL of pure water or hydrogen peroxide aqueous solution (concentration: 5% by volume or 10% by volume) was poured into a fluororesin insert container (inner diameter: 24 mm, depth: 120 mm, internal volume: 50 mL). 2. The support container was inserted into the insert container with 0.5 g of manganese carbonate particles (Kojundo Chemical Laboratory Co., Ltd.) placed on it. The support container was structured as a polytetrafluoroethylene support rod (diameter: 20.6 mm, height: 70.5 mm) with a recess (diameter: 15 mm, depth: 17 mm) at the top end. The manganese carbonate particles were placed in this recess. 3. The insert vessel was capped and sealed in a stainless steel pressure vessel (DAB-2, Berghof). 4. The reaction vessel was placed in an incubator (ST-120, Espec Corporation). In this state, it was heated at 100 to 200° C. for 0.5 to 6 hours. The pressure inside the reaction vessel reached a maximum of 1.7 MPa. 5. The inside of the reaction vessel was cooled to room temperature. The obtained particles were washed with water and separated into solid and liquid using a centrifuge (LCX-100, Tommy Seiko Co., Ltd.), and dried at 100° C. In this way, an aggregate of manganese oxyhydroxide particles was obtained.
[0027] [Evaluation method] (1) Observation of particle shape The shape was observed using a scanning electron microscope (JSM-6010LA, JEOL Ltd.) under the following observation conditions: magnification: 3000 times, applied voltage: 5 kV.
[0028] (2) Crystalline phase and crystalline phase fraction The crystal phase was identified and the crystal phase fraction was calculated using a powder X-ray diffractometer (D2 PHASER, Bruker). The measurement conditions were: X-ray irradiation: CuKα ray, scanning range: 2θ = 10 to 90°, step width: 0.02°, scanning speed: 0.5 s / step.
[0029] [result] Figure 1 shows SEM images of the aggregates reacted with different heating times (hydrogen peroxide aqueous solution concentration: 5 volume%, heating temperature: 200°C). As can be seen from the figure, the surface shape of the particles changed as the reaction progressed, and needle-like structures appeared.
[0030] The left panel of Figure 2 shows the production rate of manganese oxyhydroxide when the concentration of the aqueous hydrogen peroxide solution and the heating temperature were changed (heating time: 2 hours). The right panel of Figure 2 shows the crystalline phase fraction when the heating time was changed (aqueous hydrogen peroxide concentration: 5 volume %, heating temperature: 200°C). As can be seen from the left panel, the production rate of manganese oxyhydroxide reached a maximum of approximately 80%. In addition, as can be seen from the right panel, by heating over a long period of time, the crystalline phase of the obtained particles became almost entirely manganese oxyhydroxide.
[0031] Example 2 An aggregate of manganese oxyhydroxide particles was produced using a compression molded body of manganese carbonate particles as a raw material. The specific procedure was as follows. 1. Manganese carbonate particles were synthesized and compression molded to obtain a manganese carbonate particle compression molded body (diameter: 20 mm, thickness: 3 mm). The manganese carbonate particles used had a particle size distribution of 0.4 to 10 μm and a median diameter (D 50 ): Spherical particles of 2 to 3 μm. Details of step 1 are as previously published by the present inventors (Takahiro Kozawa, op.cit.). 2. 20 mL of pure water or hydrogen peroxide aqueous solution (concentration: 5 to 30% by volume) was poured into a fluororesin insert container (inner diameter: 51 mm, depth: 115 mm, internal volume: 250 mL). 3. An Al2O3 disk (diameter: 40 mm, thickness: 3.4 mm) was placed on a polytetrafluoroethylene tube (height: 55 mm). A compression molded body of manganese carbonate particles was placed on the Al2O3 disk. In this state, the compression molded body was inserted into the insert container. 4. The insert vessel was capped and sealed in a stainless steel pressure vessel (DAB-2, Berghof). 5. The reaction vessel was placed in an incubator and heated at 100 to 200° C. for 2 to 16 hours. The pressure inside the reaction vessel reached a maximum of 1.7 MPa. 6. The inside of the reaction vessel was cooled to room temperature. The obtained aggregate was dried at 100°C. In this manner, an aggregate of manganese oxyhydroxide particles was obtained. This aggregate was a porous aggregate.
[0032] [Evaluation method] (1) Observation of aggregate surfaces The surfaces of the aggregates were observed with a scanning electron microscope in the same manner as in Example 1.
[0033] (2) Crystal phase The crystal phase was identified using a powder X-ray diffractometer in the same manner as in Example 1.
[0034] (3) Pore size distribution The pore size distribution of the aggregates was evaluated using a mercury porosimeter (AutoPore V 9620, Micrometrics Instrument Corporation). The measurement conditions were: surface tension of mercury: 485 dynes / cm, contact angle of mercury: 130°, injection pressure of mercury: 0.5 psia, and measurement pressure: 0.5–60,000 psia.
[0035] [result] Figure 3 shows SEM images of aggregates reacted with different concentrations of aqueous hydrogen peroxide (heating temperature: 200°C, heating time: 12 hours). Figure 4 shows SEM images of aggregates reacted with different heating times (aqueous hydrogen peroxide concentration: 10 volume%, heating temperature: 200°C). As can be seen from these figures, in a system that has come into contact with hydrogen peroxide, needle-like structures appear if the reaction is allowed to proceed for a sufficient period of time.
[0036] FIG. 5 shows XRD spectra obtained when the concentration of the aqueous hydrogen peroxide solution and the heating time were changed (aqueous hydrogen peroxide solution concentration: 5% or 10% by volume, heating temperature: 200°C). As can be seen from the figure, in a system in which the concentration of the aqueous hydrogen peroxide solution was 5% by volume, no peaks derived from anything other than manganese oxyhydroxide were observed after heating for 8 hours or more. Similarly, in a system in which the concentration of the aqueous hydrogen peroxide solution was 10% by volume, no peaks derived from anything other than manganese oxyhydroxide were observed after heating for 4 hours or more. From these results, if the concentration of the aqueous hydrogen peroxide solution is in the range of 5 to 10% by volume, almost all of the crystals will become manganese oxyhydroxide if the reaction is allowed to proceed for a sufficient period of time.
[0037] Figure 6 shows the XRD spectrum when the hydrogen peroxide concentration was changed (heating temperature: 200°C, heating time: 12 hours). As can be seen from the figure, when the concentration of the hydrogen peroxide solution was further increased, some crystals of dehydrated manganese oxyhydroxide were observed, but manganese oxyhydroxide was still produced. It should be noted, however, that by changing conditions such as the heating temperature, heating time, and volume of the reaction vessel, it is expected that almost all of the crystals will become manganese oxyhydroxide, even if a 20% or 30% by volume aqueous hydrogen peroxide solution is used in the reaction. On the other hand, in the system in which pure water was used in place of the aqueous hydrogen peroxide solution, almost no manganese oxyhydroxide peaks were observed.
[0038] The results shown in Figures 5 and 6 were obtained from samples prepared by crushing the entire aggregates. This shows that the aggregates obtained in Example 2 were converted to manganese oxyhydroxide not only on the surface but also inside.
[0039] Figure 7 shows the pore size distribution when the hydrogen peroxide concentration was changed (heating temperature: 200°C, heating time: 12 hours). As can be seen from the figure, the pore size distribution changed when the hydrogen peroxide aqueous solution concentration was changed. It is believed that the pore size distribution also changes when conditions such as the heating temperature, heating time, and volume of the reaction vessel are changed.
[0040] Example 3 The porous aggregates were used as filters to capture lithium in the solution. The specific procedure is as follows. 1. An aggregate of manganese oxyhydroxide particles was prepared by the same procedure as in Example 2. The aggregate was porous. 2. A porous aggregate (diameter: 20 mm, thickness: 1.5 mm) was placed in a simple filtration device. 3. Ethanol solution of LiNO3 and NaOH (Li + CO2 gas was blown into the solution (concentration: 0.1 g / L) to precipitate Li2CO3 nanoparticles. 4. Under reduced pressure, the dispersion of Li2CO3 nanoparticles was introduced into a simple filtration device. 5. The filtered porous aggregate was dried at 100° C., and then further heated at 600° C. for 2 hours.
[0041] [Evaluation method] (1) Observation of aggregate surfaces The surfaces of the porous aggregates were observed visually and with a scanning electron microscope in the same manner as in Example 1.
[0042] (2) Crystal phase The crystal phase was identified using a powder X-ray diffractometer in the same manner as in Example 1.
[0043] [result] Figure 8 shows the appearance of the aggregates. The porous aggregates were brown before being used as filters (panel a). The surface then turned white due to the capture of Li2CO3 (panel b). When the aggregates were further heated in this state, the areas containing excess lithium turned black (panel c).
[0044] SEM images of the aggregates are shown in Figure 9. As can be seen from the cross-sectional image of the aggregate that trapped Li2CO3 (corresponding to panel b of Figure 8), a layer of trapped Li2CO3 was formed on the surface of the aggregate. As can be seen from the surface image of the aggregate that was heated after trapping Li2CO3 (corresponding to panel c of Figure 8), the structure of the needle-like particle aggregate was still maintained at this point.
[0045] XRD analysis showed that when the agglomerates were heated after trapping Li2CO3, lithium manganate (Li-Mn-O) formed on the lithium-rich surface, while Mn2O3 formed in the lithium-poor interior of the agglomerates. [Industrial Applicability]
[0046] The present invention can be used for producing metal oxyhydroxides, etc.
Claims
1. An aggregate of metal oxyhydroxide particles, The metal is a metal that can have an oxidation number +III. Aggregates.
2. The metal that can have an oxidation number of +III is one or more selected from the group consisting of manganese, cobalt, iron, aluminum, nickel and vanadium. The aggregate of claim 1.
3. The metal oxyhydroxide particles are acicular particles. The aggregate of claim 1.
4. The aspect ratio (ratio of major axis / minor axis) of the acicular particles is 3 or more. The aggregate of claim 3.
5. The maximum diameter of the aggregate is 1 mm or more. The aggregate of claim 1.
6. 1. A method for producing a metal oxyhydroxide, comprising the step of heating a metal carbonate under pressure and in an atmosphere of hydrogen peroxide vapor, The metal carbonate is a carbonate of a metal that can have an oxidation number +III. Manufacturing method.
7. The metal that can have an oxidation number of +III is one or more selected from the group consisting of manganese, cobalt, iron, aluminum, nickel and vanadium. The method according to claim 6.
8. The metal oxyhydroxide is in the form of particles or aggregates thereof. The method according to claim 6.
9. The particles are acicular particles. The method according to claim 8.
10. The aspect ratio (ratio of major axis / minor axis) of the acicular particles is 3 or more. The method of claim 9.
11. The maximum diameter of the aggregate is 1 mm or more. The method according to claim 8.
Citation Information
Patent Citations
Manganese oxyhydroxide, method for preparing the same and lithium-manganese compound oxide using the same
JP2011105538A